2002
DOI: 10.1093/protein/15.10.835
|View full text |Cite
|
Sign up to set email alerts
|

Engineering streptococcal protein G for increased alkaline stability

Abstract: Most protein-based affinity chromatography media are very sensitive towards alkaline treatment, which is a preferred method for regeneration and removal of contaminants from the purification devices in industrial applications. In a previous study, we concluded that a simple and straightforward strategy consisting of replacing asparagine residues could improve the stability towards alkaline conditions. In this study, we have shown the potential of this rationale by stabilizing an IgG-binding domain of streptoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 44 publications
3
43
1
Order By: Relevance
“…13 The Z wt domain was derived from the B domain of SpA. Plasmid pAC2dimer, encoding a head-to-tail dimer of the WT C2 domain of Streptococcal protein G, 48 was used as the template for PCR amplification of the C2 encoding gene fragment, using primers introducing an upstream ClaI site and a downstream stop codon followed by an XhoI site (upstream primer sequence, 5 0 -3 0 : GGGCCATCGATCA CTTACAAACTTGTTATTAAT; downstream primer sequence, 5 0 -3 0 : GGGCTCGAGTTATTCAGTAACTGTAAA GGTCTT). Recombinant Ad fiber R7-C2-C2 (Figure 1c) Antibody-binding Ad for targeted gene delivery P Henning et al was constructed by genetically replacing the Z wt -Z wt motif in R7-Z wt -Z wt with the dimeric C2 IgG-binding motif, using the ClaI and XhoI restriction sites.…”
Section: Generation and Nomenclature Of Recombinant Fibersmentioning
confidence: 99%
“…13 The Z wt domain was derived from the B domain of SpA. Plasmid pAC2dimer, encoding a head-to-tail dimer of the WT C2 domain of Streptococcal protein G, 48 was used as the template for PCR amplification of the C2 encoding gene fragment, using primers introducing an upstream ClaI site and a downstream stop codon followed by an XhoI site (upstream primer sequence, 5 0 -3 0 : GGGCCATCGATCA CTTACAAACTTGTTATTAAT; downstream primer sequence, 5 0 -3 0 : GGGCTCGAGTTATTCAGTAACTGTAAA GGTCTT). Recombinant Ad fiber R7-C2-C2 (Figure 1c) Antibody-binding Ad for targeted gene delivery P Henning et al was constructed by genetically replacing the Z wt -Z wt motif in R7-Z wt -Z wt with the dimeric C2 IgG-binding motif, using the ClaI and XhoI restriction sites.…”
Section: Generation and Nomenclature Of Recombinant Fibersmentioning
confidence: 99%
“…Furthermore, the interactions between SPG and Fc involve many charged and polar residues, forming hydrogen bonds and salt bridges while the binding between SPA and Fc involve mostly hydrophobic interactions (Sauer-Eriksson et al 1995). The strength of the binding to Fc has been determined using SPR to around 20-100 nM for the C2-domain and low nanomolar values for the whole SPG molecule have been reported (Akerstrom & Bjorck 1986;Gulich et al 2002;Sagawa et al 2005). The binding of SPA and SPG to Fc is pH-dependent.…”
Section: Streptococcal Protein Gmentioning
confidence: 99%
“…The alkali stabilized albumin-binding domain provides a robust affinity ligand for purification or depletion of albumin from for example serum to facilitate detection of low abundant biomarkers (Eriksson et al 2010;Linhult et al 2003). Furthermore, the strategy for increasing tolerance to alkali has proven effective also when applied to the Z-domain (Linhult et al 2004) and the C2-domain (Gulich et al 2002). The strategies employed to those domains evaluated, apart from asparagine residues, also replacements of glutamine residues, and showed that all replacements have to be evaluated on a case-by-case basis.…”
Section: Protein Engineering To Address Stability and Its Implicationmentioning
confidence: 99%
“…SpG binds the Fc regions of IgG from many mammalian species [1]. Sloan and collaborators reported that the primary amino acid sequence of the IgG-binding domains (C1, C2, and C3) of SpG are not homologous to those of the corresponding areas (E, D, A, B and C) of Staphylococcal protein-A (SpA) [2].…”
Section: Introductionmentioning
confidence: 99%